Is Belief in God Related to Differences in Adolescents' Psychological Functioning?. Issue 1 (5th July 2016) - Huuskes, Lee M.; Heaven, Patrick C. L.; Ciarrochi, Joseph; Parker, Philip; Caltabiano, Nerina
Abstract : Many studies have documented links between positive psychological functioning and religiousness during the adolescent years, but very few have contrasted religious and nonreligious youth. The purpose of the present study was to examine differences in psychological functioning among adolescent atheists, agnostics, and believers using a profile analysis approach. The authors conducted a survey of Grade 8 students (N = 1, 925) enrolled in Catholic schools in two Australian states. The survey included 10 measures of psychological functioning, broadly divided into three categories (positive adjustment, social well‐being, and negative outcomes). Results indicated that belief in God was related to distinct profiles of psychological adjustment. The implications of these findings for understanding how differing value systems are related to particular developmental stages are discussed.